EVALUASI PENYUSUNAN ANGGARAN PADA PEMERINTAH DESA KAUNERAN KECAMATAN SONDER KABUPATEN MINAHASA - Menajang, Tirsa Alicia; Saerang, David P. E.; Runtu, Treesje (Universitas Sam Ratulangi, 2018)
Budget is an important part in achieving the objectives and planning activities that will be implemented in the government. The existence of budgeting on a village can be a guideline for the village government in the planning of the development activity program for the year. Budget drafting in the Kauneran village Sonder district of Minahasa regency discussed with the government, community and related parties, so that the formation of activities program aims for development and welfare of village communities. In the process of budget drafting, evaluation is needed as accountability of the village finances so that the budget becomes very important. This study aims to evaluate the process of budget preparation at the government of Kauneran village Sonder district of Minahasa regency. The data analysis used is descriptive analysis with qualitative approach. The results of the research shows that process of preparing the budget of Kauneran Village Government Minahasa regency is accordance with government regulations in force.Keywords: Budget drafting, Evaluation